Evaluation of the Implementation of Internal Control in the Business Processes of Public Appraisal Firm JD Using COSO (2013) - Anggo Prima Virgantara; Purwatiningsih Lisdiono (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to evaluate the implementation of internal control within the business processes of the Public Appraisal Services Office (KJPP) JD using the COSO Internal Control - Integrated Framework (2013). A descriptive qualitative approach was adopted through a case study method. Data were collected through interviews, observations, and documentation related to the core business processes of KJPP JD, including pre-engagement, assignment execution, and post-engagement stages. The evaluation reveals that KJPP JD has generally implemented the five key components of internal control as outlined in the COSO framework: control environment, risk assessment, control activities, information and communication, and monitoring activities. However, several weaknesses were identified, particularly in the formal documentation of policies and procedures, as well as the lack of periodic risk assessments. Recommended improvements focus on enhancing governance through better documentation, employee training, and strengthening internal monitoring functions. This research is expected to contribute to improving the effectiveness of internal control in the professional services sector, particularly in appraisal services.